Physical performance and game demands in beach volleyball: A systematic review - Marzano-Felisatti, J. M.; Pino-Ortega, J.; Priego-Quesada, J. I.; Guzmán Luján, J. F.; García de Alcaraz, A. (Journal of Human Sport & Exercise, 2025)
The physical-conditional aspects of the game are a significant research area, focusing on game demands, strength, and kinematic features. This study aimed to synthesise the current state of the art regarding beach volleyball's physical demands. This systematic literature review was conducted in March 2024, following the PRISMA criteria and methodological quality scales. The databases consulted were SPORTDiscus, Web of Science, and Scopus. Data concerning study design, sample size, gender, age-group category, player role, and performance level were considered. The risk of bias was assessed using the 12-item MINORS methodological index scale. A total of 19 studies were included, considering male (6), female (9) or both genders (4) as a sample. According to the athletes` level of performance, 25% of the studies assessed players at the developmental or national level, 50% explored the international context, and the remaining 25% were with elite players. Data regarding game demands, mechanical outcomes related to jump and power, kinematic variables concerning distance covered and running speed, and kinetic measurements for acceleration and deceleration actions are displayed. The data provided by the current review allow a precise comparison, addressing specific performance profiles and future research challenges from the lack of knowledge about this topic.